A Critical Review of Archaeology and History of Third Millennium Iran - Hasan Basafa; Mohammad Sadeghdavari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book "Archeology of Ancient Iranian societies in the Third Millennium B.C” is one of the specialized books about the third millennium archeology of the Iranian plateau with a special look into the southeastern region of Iran. This book is written by "Enrico Ascalone", translated by "Seyed Mansour Seyed Sajadi" and published by the Organization for Researching and Composing University Textbooks in the Humanities with the aim of being lectured as the main or supplementary source for the course-"Iranian Archaeology at the Beginning of Urbanization". What is mentioned in the introduction of the book by the author is the identification of the cultural poles of Iran's plateau during the third millennium B.C, the degree of repulsion and attraction between those poles, and then the study of the special fields of trade. In this regard, the analysis of the business systems with Susa centrality-as an Elamite unit-was his aim. The present paper tries to study and analyze the book in terms of its form and content-especially formal comprehensiveness, logical order and principles-according to the author's approach, which is of analytical approaches to urban archeology and finally its strengths and weaknesses are explained. The results indicate many merits in terms of content and respect for the authoring principles of an impartial work. On the other hand, the book has weaknesses in translation, editing and matching of specialized terminology, the use of archaeological resources, and archaeological fundamentals of the peripheral regions of Iranian Plateau.